Interoperabilidade semântica orientada por ontologia para a Ciência da Informação: a metodologia Onto4All-Interoperability como resultado de estudo de caso no domínio de energia - Jeanne Louize Emygdio (2021)
The quality of the information digitally exchanged is equivalent to the precision used in representing reality for storage and retrieval purposes. Such an effort must comprise exhaustive discussions on a heterogeneous myriad of information to enable its capture, understanding, organization, accurate representation, and, consequently, efficiency in retrieval. Since such practices are not known and applied, obstacles remain that make the semantic retrieval of information unfeasible, even with technological evolution. This research contemplates a theoretical, empirical, and methodological study of interoperability and ontologies in their multiple specificities. The research is justified by: i) the lack of understanding about the scope of the two themes mentioned and the contributions that the applied ontology offers to the demands of interoperability; ii) the characteristics that make ontology a preferred resource for designing interoperability architectures and data integration systems; iii) the aspects that favor efficient and economical data management concerning the technologies adopted by the organizations; iv) the plenty of approaches, methods, techniques and information technologies that must be articulated in interoperability solutions; v) the gap in high-level knowledge representation in the electricity sector; vi) the Information Science expertise in knowledge representation and information retrieval, providing solutions for other scientific fields, including in the scope of semantic interoperability. This research is characterized as scientific research in the field of information: i) applied research; ii) qualitative research; iii) explanatory research, and iv) case study. The general objective of the research was to reach a methodology to support interoperability based on ontology as a result of a practical experiment in the Brazilian electricity sector. As specific objectives, the following were established: i) to design an interoperability architecture based on the articulation of ontological approaches; ii) validate the designed architecture in a practical experiment and iii) consolidate the results obtained into a methodology. As research contributions, the following are cited, among others: i) the Onto4all-Interoperability Methodology: a semantic interoperability methodology based on ontology, conceived for Information Science; ii) multidisciplinary theoretical contributions on interoperability in its multiple aspects; iii) multidisciplinary theoretical contributions on ontology-based semantic interoperability approaches, methods, and techniques; iv) case study in an unprecedented domain in the country, with practical application of the methodology; v) the availability of templates for replication of the methodology; vi) domain ontology enrichment, from the aggregation of new resources; vii) additional theoretical contributions on aspects of databases, relational algebra and descriptive logic, indispensable to discussions about the challenges of interoperability in information systems in organizations.